The Students' Motivation and Achievement in Learning English: The Correlational Study - Asrifan, Andi; T. Zita, Cris; Abd Al-Lateef, Ghada Tosson; Enriquez, Alexis Arizabal; Muthmainnah, Muthmainnah; Al-Matari, Ali Said (Journal of Education, Language Innovation, and Applied Linguistics, 2023)
The students have a lot on their plates already, and one of the biggest is the academic activity. Researchers have shown a correlation between intrinsic motivation and academic performance. Students' English proficiency is also influenced by their level of interest and effort in learning the language. The purpose of this research was to determine if and how students at MA Muhammadiyah Darul Arqam Punnia Labumpung, Kab. Pinrang is motivated to learn English based on their academic performance. Students' interest in English and effort in studying the language were found to be significantly related. This was demonstrated by a correlational study on students' motivation and their performance on an English language test. The first piece of good news is that the SPSS 21 program's computed r value is greater than the table at both the 5% and 1% significant level (0.367 0.852 > 0.47). Second, the computation of the contribution between student motivation and achievement in English showed that student motivation (variable X) contributed roughly 72.59% contribution to the achievement (variable Y) of the sample class, while the remaining 25.41% was influenced by other factors. Keywords: Students’ Motivation, Learning English, and English Achievement.